PENGARUH DISIPLIN KERJA, KEMAMPUAN KERJA DAN FASILITAS KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR PELAYANAN PAJAK PRATAMA MEDAN TIMUR - Baginda Simatupang; Marudut Sianturi; Jonner Lumban Gaol (JURNAL PROINTEGRITA, 2021)
There are many factors that can affect performance, but this study only examines factors of work discipline, work ability factors and work facilities factors. This study aims at determining the effect of work discipline variables, work ability variables and work facilities partially and simultaneously on the performance of employees at the East Medan Primary Tax Office. The population of this research is 113 employees. To determine the number of samples used the Slovin formula so that the sample is 53 employees. Data collection techniques in this study are questionnaires, interviews and documentation studies. While the data analysis technique used is the classical assumption test, multiple regression, t test, F test and the coefficient of determination. The results show that the work discipline variable has a significant effect on the performance of the employees at the East Medan Primary Tax Office, where the higher the work discipline, the better the employee's performance. The work ability variable has a significant effect on the performance of employees at the East Medan Primary Tax Office, where the higher the work ability, the better the employee's performance. The work facility variable has a significant influence on the performance of the employees at the East Medan Primary Tax Office, where the better the work facilities, the better the employee's performance. There is a significant influence on work discipline variables, work ability variables and work facilities variables on employee performance at the East Medan Primary Tax Office. The coefficient of determination is 88.40%, the variation in employee performance is explained by work discipline variables, work ability variables, and work facilities variables simultaneously, and the remaining 11.60% is explained by other factors such as organizational climate variables and leadership. It is recommended that leaders in agencies need to provide an example of discipline and assertiveness in making decisions so that work discipline in agencies can be better. In this case, every employee committing disciplinary violations, both minor and serious, must be given strict sanctions. Leaders in agencies need to make efforts so that employees have sufficient experience in their field of work and place employees in positions that are in accordance with their work experience. In this case, employees need to be given the opportunity to attend training such as training in accordance with the field of work of each employee. Agencies need to organize offices with more comfortable decorations, and also need to provide more adequate office equipment and supplies for employees to use by using the agency's budget. It is necessary to improve employee discipline and make more efforts to improve employee abilities because these variables are classified as weaker than the work facility variable. Other researchers need to do further research by using more independent variables on employee performance.